Low power digital integrated circuit design using energy recovery technique - Billy Wiguna Widjaja. (2008)
In this dissertation, two new adiabatic logic designs are proposed, namely IAPDL-2 (Improved Adiabatic Pseudo-Domino Logic 2) and MDIAPDL-HT (Modified Dual-Rail Improved Adiabatic Pseudo-Domino Logic with High Throughput).